A Process for Assessment and Quality Improvement of the Clerkship Curriculum. (February 2019) - Glaser, Kelli
Reliance on the apprenticeship model of education in the clerkship years of medical education persists despite concerns with variability in educational delivery and outcomes. Although many institutions are addressing this variability, there needs to be a clear and objective method to assess what is working. Evaluating these educational experiences is an essential component to ensure that students graduate prepared to enter residency. In 2014, A.T. Still University's School of Osteopathic Medicine in Arizona (ATSU-SOMA) introduced a curricular change to address clerkship variability by implementing an online curricular component for the core clerkship courses in the third and fourth years of medical student education. Subsequently, a new structured and objective process to evaluate these courses was designed to improve student learning outcomes in the clerkship years. A Curriculum Year Three and Four Work Group was created to develop the new process for curricular evaluation of the clerkship courses. In the pilot phase of its implementation, described herein, the process fostered stakeholder participation and buy-in, enhanced communication of expectations, increased accountability in clerkship course design, and effectively employed objective evaluation tools in determining what curricular changes were needed. The Curriculum Year Three and Four Work Group continues to revise the tools and methods to enhance the efficiency of the evaluation process and to analyze whether recommended course revisions have improved student outcomes.